Cognitive impairment in neuromyelitis optica spectrum disorders - E. A. Vekhina; D. S. Kasatkin; S. E. Korchevnyi; K. I. Bereznyak (Неврология, нейропсихиатрия, психосоматика)
Neuromyelitis optica spectrum disorders (NMOSD) are a group of immune-mediated inflammatory lesions of the central nervous system that primarily cause dysfunction and death of astrocytes, leading to secondary disruption of myelination. The optic nerve, the spinal cord, the brain stem (periventricular and periaqueductal space) and the diencephalon are most frequently affected sites. According to a meta-analysis of 25 studies, the prevalence of cognitive impairment (CI) in 761 patients with NMOSD aged 34 to 53 years was between 3 and 75%, after adjustment this figure was 34%. The most frequently observed CI in NMOSD are decreased attention and working memory function, reduced information processing speed and impaired verbal memory and fluency. A significant influence on the severity of CI in NMOSD have the patient's age, the duration of the disease, the level of education, the degree of disability and the severity of upper and lower limb dysfunction. The data collected suggest that neurodegenerative disorders, including CI, are characteristic of this pathology. The pathogenesis of CI in NMOSD is very complex and involves both mechanisms of direct damage to structures that perform cognitive functions (hippocampus, prefontal cortex) and immunological aspects (microglia, complement, interleukin 6), which requires further investigation.